Pemberian Rewards untuk Meningkatkan Academic Performance Matematika di Sekolah Dasar - Apriani Wulandari; Syifa Zam Zami Nurjono; Yunisa Larasati; Cintia Devi Johan; Nurlaela Larasandi; Rizma Afian Azhiim (CV. ITTC INDONESIA, 2026)
Low academic performance in mathematics among elementary school students is often associated with the perception that mathematics is difficult and less interesting. One effort to improve learning outcomes is the use of rewards as positive reinforcement for students learning behavior. This study aims to examine the effect of reward provision on elementary school students mathematics academic performance. A quasi-experimental method with a pre-test and post-test control group design was used. The participants were 58 first-grade students, divided into an experimental class (1D) and a control class (1B). Sticker rewards were given to students who obtained scores above the class average for four weeks. Data were collected from daily assignment scores before and after the intervention. The data were analyzed using a t-test with a significance level of 0.05.